Pendayagunaan Multimedia dalam Pengajaran Bahasa Arab - Armawi, Sullati (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2018)
The article describes about role of multimedia in teaching Arabic in terms of principles of choosing medias, selection the proper media as well as the prominent strategic that can be used in developing the multimedia itself. Currently, it is shown that learning the second languages such as Arabic is classified as hard effort. There are so many methods that have been selected by teachers in designing attractive learning in order to stimulate the students’ interest in class. Therefore, multimedia as a tool not only can deliver the proper message to learner but also it ensures to achieve the learning goals in purposes. Difference of learning styles, intelligence, disability, distance, time and so on, can be solved by using the correct multimedia.